PERBEDAAN PENDAPATAN PETANI PADI PENGGUNA MESIN PANEN POWER THRESHER DAN MESIN PANEN COMBINE HARVESTER DI KECAMATAN PANCA RIJANG KABUPATEN SIDRAP - Sarro, Dastar (Katalogis, 2015)
Handling the rice harvest has contributee to the national rice production. Crop yield losses due to handling imperfect reached 20.51%. If the national rice production reached 54.34 million tons, then the loss is equivalent to Rp15 trillion. Therefore, this study aims to compare the income of rice farmers between power thresher harvester machine users and combine harvester machine users in sub district panca rijang in the district of sidrap. This includes how to harvest, cutting, gathering and threshing of grain as well as differences in the wage system. The total population of this study was 1.060, which include 53 the combined farmer groups (Gapoktan). In addition, each combined farmer groups consist of 20 and it was randomly taken of 5 farmers. This study applying calculation formula by 26.5 x 5 = 132.5. Then, it was devided by 2 so that there were 66 refresented farmers of thresher power users and combine harvester rice farmers users respectively. Following that, Slovin formula was used by nominating 39.75 respondents or rounded by 80 respondents. The data was collected through documentation, interviews and questionnaires. The cost and the profit of farmers can be determined by using analytical tools, such as, Ï€ = TR - TC. The hypotheses were tested by using different test independent and paired difference test (SPSS version 18). This study found that the income of rice Â farmers who applied power thresher was Rp. 17,503,733.36 / ha, while rice farmers combine harvester users was Rp. 22,095,914.38 / ha. There was high proportion of the income of rice farmers by 26.2% / ha. The output of SPSS version 18 shows a probability value of 0.000 <0.05 at 95% confidence level test in both directions. This means that this study reject the null hypothesis. Thus, Â there is a significant difference of the rice farmers income between power thresher harvesting machine users and combine harvester machine users.